2003
DOI: 10.1039/b308042k
|View full text |Cite
|
Sign up to set email alerts
|

A highly enantioselective phase-transfer catalyzed epoxidation of enones with a mild oxidant, trichloroisocyanuric acidElectronic supplementary information (ESI) available: experimental details. See http://www.rsc.org/suppdata/cc/b3/b308042k/

Abstract: The enantioselective epoxidation can be carried out using trichloroisocyanuric acid (TCCA) as oxidant in the presence of chiral quaternary ammonium salt as a phase-transfer catalyst; treatment of chalcone derivatives with TCCA under mild conditions afforded the corresponding epoxy ketones in good yields with moderate to excellent enantioselectivities of up to 96%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 15 publications
0
14
0
3
Order By: Relevance
“…In the presence of 10 mol % of chiral catalyst A2, the asymmetric epoxidation of enones under non-aqueous solid-liquid conditions provided the epoxy ketones in 73 ± 93% ees and 76 ± 94% yields. Although the ees are similar to or slightly lower than those obtained under liquid-liquid conditions, [8] the yields are good in almost all cases. Coupled with the fact that the product separation is more convenient excluding the wet viscid isocyanuric acid, we believe that this new non-aqueous procedure holds considerable promise for the future applications.…”
Section: Full Papersmentioning
confidence: 81%
See 2 more Smart Citations
“…In the presence of 10 mol % of chiral catalyst A2, the asymmetric epoxidation of enones under non-aqueous solid-liquid conditions provided the epoxy ketones in 73 ± 93% ees and 76 ± 94% yields. Although the ees are similar to or slightly lower than those obtained under liquid-liquid conditions, [8] the yields are good in almost all cases. Coupled with the fact that the product separation is more convenient excluding the wet viscid isocyanuric acid, we believe that this new non-aqueous procedure holds considerable promise for the future applications.…”
Section: Full Papersmentioning
confidence: 81%
“…[10] This process can take place under basic conditions as well and produce aqueous hypochlorite salt, which is a mild oxidant for the asymmetric epoxidation of a,b-enones under liquid-liquid phase-transfer catalytic conditions. [8] Interestingly, we found that this epoxidation could occur under non-aqueous conditions when using solid potassium hydroxide instead of its aqueous solution, and the reaction procedure is more convenient for product separation excluding the wet viscid isocyanuric acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A somewhat limited applicability of this system was observed with less-reactive enones, such as those which bore an alkyl group at the carbonyl position and which required long reaction times so [46]. Subsequently, trichloroisocyanuric acid (TCCA) was shown to be an alternative for use with catalyst 46, as a safe and inexpensive oxygen source [47]. Corey suggested a model to account for the formation of the (αS, βR)-enantiomer of the product in the epoxidation of trans-chalcones promoted by catalyst 46 (Figure 9.8).…”
Section: Phase-transfer Catalystsmentioning
confidence: 99%
“…Recently, we have reported that a novel oxidation system, trichloroisocyanuric acid (TCCA) with an inorganic base such as potassium hydroxide, could serve as an efficient alternative for these oxidants in the epoxidation of enones with high activity and enantioselectivity under chiral phase-transfer conditions. [10] It is well known that the Claisen-Schmidt condensation (CSC) is a convenient method for the synthesis of enones. The reaction of a ketone and an aldehyde can occur under aqueous or alcoholic alkaline conditions.…”
mentioning
confidence: 99%